Biological Responses Of Inhaling Gas And Particulate Matter From Biomass Burning On The Respiratory System Of Rats - Widiyanto, Slamet (2003)
Trans-boundary air pollution from biomass burning like forest fire is a recurrent environmental problem in Southeast Asia. This raises inevitable issues of the impact of increasing air pollution on human health. Biomass burning releases large amounts of particulates (solid carbon combustion particulates) and gases. Uncontrolled forest fire in Southeast Asia especially Indonesia and Malaysia has caused smoke pollution (haze). The haze episodes in Southeast Asia contributed to substantial health problem of the public in 1 997 and early 1 998. Exposure to gas and particulate air pollution resulted in adverse health effects i.e. an increase in the morbidity and mortality due to respiratory and cardiovascular diseases however the biological mechanisms responsible for this association are not clear.